Combined Effect of Abusive Supervision and Abusive Supervision Climate on Employee Creativity: A Moderated Mediation Model - Shen, Chuangang; Yang, Jing; Hu, Sanman (Frontiers in Psychology, 2020)
In accordance with social comparison theory and social identity theory, a multi-level model is put forward to investigate how the “conjoint” associations between abusive supervision and abusive supervision climate exert influence on employee creativity in the view of individual-level through the process of creative role identify. The data in this paper were from 357 supervisor-subordinate paired questionnaires in 77 working groups to test the proposed model. The substantiated consequences indicated that creative role identity can play its mediating mechanism to mediate associations between abusive supervision and employee creativity, acting as a cross-level moderator, abusive supervision climate may moderate the relationship between creativity and individual-level abusive supervision through the process of creative role identity, the mutual influence of abusive supervision climate and individual-level abusive supervision may significantly predicate employee creativity. This paper also discusses related managerial and practical implications.